Presence of pathogenic bacteria and antimicrobial resistance in Portuguese wild ungulates - Dias, Diana Patrícia Pires (2018)
Antimicrobial resistance is as an emerging global problem in both human and veterinary medicine. In theory, wild animals are rarely exposed to antimicrobial agents and therefore low levels of AMR are to be expected. However, the growing interaction of these animals with anthropogenic activities can have a huge impact in their bacterial flora. Escherichia coli is commonly found in the intestinal tract of a wide variety of animals and humans. This intestinal bacterium can be easily disseminated in different ecosystems. Therefore, it can be an useful indicator of the selective pressure exerted by the use of antimicrobials. Salmonella is a pathogenic bacterium, commonly found in the intestine of healthy birds and mammals that can cause salmonellosis in humans. In the European Union, over 90,000 salmonellosis cases are reported every year to EFSA. This study was conducted in wild ungulates from three distinct geographical areas in Portugal (Montesinho, Idanha-a-Nova and Lousã) and aimed to: i) access the levels of antibacterial resistance occurring in E. coli strains ii) determine the occurrence levels of Salmonella spp. and iii) determine the occurrence levels of shiga toxin-producing E. coli (STEC). To that purpose, a total of 67 faecal samples from red deer (n=41), wild boar (n=21) and roe deer (n=4) were collected. Before antibacterial susceptibility testing (according to the EUCAST guidelines), the E. coli isolates obtained were typed by BOX-PCR to select for genetically different strains for each sample (n=152). The detection of Salmonella was performed according to ISO 6579:2002 Annex D. Results revealed that in E. coli resistance was observed to ampicillin (10%), tetracycline (9%), streptomycin (5%), co-trimoxazole (4%), amoxicillin/clavulanic acid (2%) and cefoxitin (1%). A total of 3.3% of the isolates exhibited a multiresistant phenotype, all from Lousã. The results were also analyzed according to ECOFFs. Non-wildtype phenotypes were obtained to ampicillin (10%), ceftazidime (6%), co-trimoxazole (4%), amoxicillin/clavulanic acid (2%), aztreonam (1%) and cefotxitin (1%). A low incidence of Salmonella spp. (1.5%) was observed and it was only identified in wild boar from Lousã. The isolate was susceptible to all the tested antimicrobials. Regarding the presence of STEC, it was possible to establish that red and roe deer from the three sampling sites carry this bacterium. The stx variants detected in the STEC isolates included stx1c, stx2d and stx2g. Moreover, the hemolysin gene ehxA was identified in a strain possessing the stx2g variant. Overall, our results reveal that these populations of wild ungulates are reservoirs of antibiotic resistant and potential pathogenic bacteria. Therefore, these animals can act as dissemination vehicles between wildlife-livestock-human interfaces.